Developing expenditure questions: Findings from R2 cognitive testing - Jo d'Ardenne; Margaret Blake (Institute for Fiscal Studies (IFS), 2012)
The Nuffield Foundation has funded a collaborative research team from NatCen Social Research, the Institute for Fiscal Studies and Oxford and Cambridge Universities to develop a standard question or questions designed to capture household spending. This is because household spending can be an indicator of household living standards and can overcome some of the limitations of income as an indicator of living standards. The project has involved conducting focus groups with people from a range of household types to explore how people thing and talk about household spending. New questions were then designed, base on existing questions but adapted to reflect the findings of the focus groups, for example that using the term household in questions about spending can be confusing. Following a reveiw of the new questions by the steering group, a round of cognitive testing was then carried out to test these questions. Key findings from round one are presented in section 1.1.2. Following the first round of cognitive testing further adaptations were made to the questions. A second round of cognitive testing was carried out to re-test the question formats which seemed most worth developing further. Additional testing was needed as a result of changes to these questions and to ensure respondents with a range of financial situations were included. This report presents the findings of this second round of cognitive testing.
Keywords: 330